Smallholder acceptance towards technologies advancement in oil palm plantation: a case study in TSK Solok Pekat, Masjid Tanah, Melaka / Haris Iskandar Mohd Suhaimi - Mohd Suhaimi, Haris Iskandar (Faculty of Plantation and Agrotechnology, 2017)
The impact of respondent’s acknowledgment alongside other level on reception of the prescribed palm oil innovation in TSK Solok Pekat, Masjid Tanah,Melaka is being studied. This study was carried out in order to determine the specific level that significantly influences adoption of recommended palm oil technology in the study area. The objective is to identify the level of awareness, affect and characteristic of adoption technology adoption in palm oil in study area. Simple random sampling procedure, (in conjunction with purposive and random sampling techniques) was used in selecting respondents for this study. Data were collected, using structured questionnaire, and analyzed, using descriptive statistics, simple linear regression, correlation and chi-square analysis (3x4). Result revealed that the respondents that accepted the technology is 49 (63.1%) and that are not accept the technology are 31 with (38.8%). The study has reveal that adopter of suggested palm oil innovation had increment the respondent level of awareness. Respondents reported that the technologies were very affordable with the mean7.06, very compatible with mean 7.06 and complex with mean 8.91. The study revealed that there is a relationship between the acceptances of recommended technology with affect of adoption the recommended technology. The conclusion of technology acceptance can increase smallholder’s income, increase the quality of oil palm and easy for smallholder to use. Most respondents agree that oil palm technologies are very complex to use. For this reason, it is recommended that non-governmental agencies should assist the smallholder by give the speech about the good of using the technology.